Wave energy dissipation due to mudbanks formed off southwest coast of India. (5th September 2017) - Samiksha, S.V.; Vethamony, P.; Rogers, W.Erick; Pednekar, P.S.; Babu, M.T.; Dineshkumar, P.K.
Abstract: Mudbanks (MBs) are a unique natural phenomenon, and form along the southwest coast of India during the southwest monsoon. They are characterized by a calm-water region, bordered by a rough sea. In order to quantify the wave energy dissipation, wave data were collected at two water depths (15 m and 7 m) before and during the period of formation of MBs off Alappuzha, Kerala. The observations indicate that MBs exist even in deeper water beyond 15 m water depth, contrary to earlier findings that they only form in depths of 0–5 m. The analysis showed 65–70% wave height attenuation. As spectral density evolves with shoaling, energy dissipation was examined using the concept of wave energy flux. The combination of high frequency dissipation and nonlinear energy transfer from higher-frequency to low-frequency waves resulted in a reduction of energy across a wide frequency range. The WAVEWATCH III® (WW3) model with wave-mud interaction physics was used to capture the signature of wave energy dissipation due to MBs. The accuracy of prediction of significant wave heights (Hs ) of the WW3 model was verified using Hs of measured waves and ERA- Interim (ECMWF Reanalysis Interim data). The model accurately reproduced both the wave heights in the MB region and their general characteristics. The measurements and model results complement each other in explaining changes associated with an apparent shift of the MBs.